Effect of Galla Chinensis on Remineralization of Early Dentin Lesion - Abdel-Azem, Hend Mahmoud; Elezz, Ahmed Fawzy Abo; Safy, Rehab Khalil (European Journal of Dentistry, 2020)
Objective This study aimed to investigate the efficacy of the Galla chinensis extract (GCE) on early dentin lesion remineralization.Materials and Methods Seventy-two dentin specimens were divided into three groups according to the treatment solution. In group S1, specimens were treated with GCE; in group S2, the specimens were treated with sodium fluoride (NaF); meanwhile, specimens of group S3 were treated with distilled water (DW). Each group was further subdivided into two subgroups according to the treatment time (1 minute and 5 minutes). An in vitro pH-cycling model for 12 days was done. Subsequently, surface microhardness (SMH) of the specimens, elemental analysis, and their micromorphological appearance were evaluated.Statistical Analysis Data were statistically analyzed. One-way analysis of variance was used to compare numerical (parametric) data between more than two separate groups followed by post hoc Tukey.Results There was no significant difference between the mean SMH of dentin between NaF and GCE groups. Regarding the time, the 5-minute treatment with NaF and DW groups recorded higher mean SMH value of dentin than the 1-minute treatment group. Meanwhile, for GCE groups, the 1-minute immersion recorded higher mean SMH value than the 5-minute immersion without any significant difference between them. The microhardness results were confirmed by environmental scanning electron microscope and energy dispersive X-ray analysis results.Conclusion GCE could be used as an effective alternative for dentin remineralization.
Keywords: dentin; demineralization; remineralization; GCE